The Dynamic of Actors' Relation to the Susceptible Condition of the Village Participatory Democracy - Taufiq, Muhammad; Hidayat, Rahmad; Sauki, Muhammad (Jurnal Pemerintahan dan Politik Lokal, 2024)
This article deals with the implementation dynamics of the Village Law in a particular context that reflects the practice of developing participatory democracy. The effective administration of village development necessitates the cultivation of a collective ethos to foster a sense of kinship and cooperation and to promote the integration of social justice principles. In essence, effective governance necessitates accountability and participation, whereby the village government is responsible for transparently reporting and justifying all development operations or programs to residents under regulations outlined in the Village Law. Furthermore, residents should be actively engaged and involved in all phases of the development process. This study employed a descriptive approach and purposive sample technique to select key informants from government officials and citizens of Soriutu Village, located in the Manggelewa District of Dompu Regency, inside the West Nusa Tenggara Province. This essay examined the dynamics of actors' relationships in the management of development activities, specifically focusing on the leadership style of the village head from 2010 to 2016. The autocratic leadership style in Soriutu Village hinders the inclusion of inhabitants in all stages of village development governance, impeding the achievement of participatory democracy. This study's findings could enhance the theoretical understanding of leadership styles, community participation, transparency, informal participation preferences, participatory democracy, deliberative democracy critiques, and optimal village development management models.